Education 3640. Problems and issues in special education. No. 19. Childhood Autism - Nesbit, W. C. (Wayne C.), 1943- (Teacher); Karagianis, Leslie D. (Teacher); Memorial University of Newfoundland. Division of Educational Technology (Producer)
Dr. Nesbit discusses the incidence and characteristics of childhood autism, its possible causes, as well as approaches to treatment and remediation. Eleanor Bragg, President of the Autism Association of Newfoundland speaks of her experience as mother of an autistic child